Exploration of Pappaseng Values in the Millenial Generation in Sidrap Regency - Siri, Hasnani; Ramli, Nurleli; Sudirman, Sudirman (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
When local wisdom is not preserved for the Millennials concerned, identity will disappear, therefore suffocating to determine the extent to which the millennial generation in Sidenreng Rappang Regency knows about the values of Nene Mallomo pappaseng. This research is qualitative with an ethnographic design. The research location focused on three Sidenreng Rappang Regency sub—districts— data collected through observations, semi-structured interviews, and documentation. The object of the study was millennia. Object selection uses purposive techniques and snowball sampling. The results showed that the millennial generation in Sidenreng Rappang Regency knows well the values of Nene Mallomo's pappaseng, which consists of lempu (honest), acca (bright), warani (brave), and getteng (opinionated). Parents, family, teachers, and the community around their home are essential in socializing these values to millennials. The school is one of the media that emphasizes their knowledge about the values of Nene Mallomo's pappaseng because it is integrated into the subject matter of local content. The condition suggests that the preservation of local wisdom needs to be strengthened in the surrounding environment so that foreign cultures do not corrupt the identity of a region.